The Relationship between Organizational Justice and Organizational Commitment with Managers Accountability in Islamic Azad University (Case Study: Islamic Azad University Branches West Mazandaran Province) - abasalt nooraee (Institute of Management fekrenoandish, 2019)
The main mission of any organization is to achieve the goals set in the framework of the organization's strategy, hence the accountability is shifting from the traditional forms of accountability to other forms, especially the more efficient and responsive management systems. The purpose of this study was to determine the relationship between organizational justice and organizational commitment with the accountability of managers and staff of Islamic Azad University of Mazandaran province. The method of this study was descriptive - correlative. The statistical population consisted of 625 staff of all Islamic Azad universities in west of Mazandaran province. The sample consisted of 209 people who were randomly selected and participated in the study. The measuring tools were Allen & Meyer's Organizational Commitment Questionnaire (1990), Niehoff & Moorman's Organizational Justice Questionnaire (1993) and Jensen's General Accountability Questionnaire (2000). The findings of this study showed that there is a relationship between organizational justice and organizational commitment and accountability of managers and staff of Islamic Azad University in west of Mazandaran province. In order to increase organizational accountability, it is advisable to provide appropriate training courses for managers to being familiarized with the principles and bases of justice, as well as to encourage them to effectively use organizational justice in the organization.